A Transient Printed Soil Decomposition Sensor Based on a Biopolymer Composite Conductor. Issue 5 (11th December 2022) - Atreya, Madhur; Desousa, Stacie; Kauzya, John‐Baptist; Williams, Evan; Hayes, Austin; Dikshit, Karan; Nielson, Jenna; Palmgren, Abigail; Khorchidian, Sara; Liu, Shangshi; Gopalakrishnan, Anupam; Bihar, Eloise; et al.
Abstract: Soil health is one of the key factors in determining the sustainability of global agricultural systems and the stability of natural ecosystems. Microbial decomposition activity plays an important role in soil health; and gaining spatiotemporal insights into this attribute is critical for understanding soil function as well as for managing soils to ensure agricultural supply, stem biodiversity loss, and mitigate climate change. Here, a novel in situ electronic soil decomposition sensor that relies on the degradation of a printed conductive composite trace utilizing the biopolymer poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyvalerate) as a binder is presented. This material responds selectively to microbially active environments with a continuously varying resistive signal that can be readily instrumented with low‐cost electronics to enable wide spatial distribution. In soil, a correlation between sensor response and intensity of microbial decomposition activity is observed and quantified by comparison with respiration rates over 14 days, showing that devices respond predictably to both static conditions and perturbations in general decomposition activity. Abstract : A novel in situ electronic soil decomposition sensor that relies on the degradation of a printed conductive composite trace utilizing a biopolymer as a binder is presented. In compost tea and soil, a correlation between sensor response and microbial decomposition activity is observed and quantified, showing that devices respond predictably to both static conditions and perturbations in general decomposition activity.